Tumor cell stemness in gastrointestinal cancer: regulation and targeted therapy - Yang, Kangqi; Yi, Tuo (Frontiers in Molecular Biosciences, 2024)
The cancer stem cells (CSCs) are a rare group of self-renewable cancer cells capable of the initiation, progression, metastasis and recurrence of gastrointestinal (GI) tumors, and also a key contributor to the therapeutic resistance. Thus, understanding the molecular mechanism of tumor stemness regulation is of great importance for targeting CSC and designing novel therapeutic strategies. In this review, we will introduce the current findings of the regulators of CSC stemness and differentiation, including the CSC surface markers, the signaling pathways and the non-coding RNAs. We will also provide a comprehensive view on how the tumor microenvironment (TME) display an overall tumorpromoting effect, including the recruitment of cancer-associated fibroblast (CAF), the construction of an immunosuppressive landscape, and the triggering of angiogenesis and hypoxia.Identification of CSC, which currently relies heavily on cell surface markers, is crucial for CSC isolation and early detection. Recent literature has selected a list of biomarker candidates highly correlated to elevated CSC phenotypes and worsened prognostic results(